Value of Pyruvate Carboxylase in Thyroid Fine-Needle Aspiration Wash-Out Fluid for Predicting Papillary Thyroid Cancer Lymph Node Metastasis - Liu, Chang; Zhang, Lu; Liu, Yang; Zhao, Qingqing; Pan, Yu; Zhang, Yifan (Frontiers in Oncology, 2021)
The incidence of papillary thyroid carcinoma (PTC) is increasing yearly. Knowing whether there is lymph node metastasis is of great value in choosing surgery and surgical methods, but ultrasound cannot qualitatively diagnose and effectively detect lymph node metastases in the central area. Metabolic dysregulation is an important factor associated with malignancy and metastasis of tumors. Pyruvate carboxylase (PC) is a major anaplerotic enzyme that catalyzes the carboxylation of pyruvate to form oxaloacetate (OAA) and is involved in tumorigenesis in several cancers. This study aims to explore the relationship between PC mRNA expression in thyroid fine-needle aspiration (FNA) wash-out fluid and lymph node metastasis of papillary thyroid carcinoma (PTC). The expression levels of PC in PTCs and normal thyroid tissues were first compared based on bioinformatics analysis of public databases, including the Gene Expression Profiling (GEPIA), Oncomine and Gene Expression Omnibus (GEO) databases. Then, the PC mRNA levels were measured by RT-PCR in surgical tissues in a total of 42 patients with surgically confirmed PTC and compared to those of patients with and without central lymph nodal metastasis (CLNM). Further, to identify PC expression in diagnostic biopsies, a total of 71 thyroid nodule patients with ultrasound-guided fine-needle aspiration wash-out fluid samples and cytological diagnosis were prospectively enrolled in the study. The findings of this study suggest that PC may predict malignancy in thyroid nodules and lymph nodal metastasis with thyroid FNA wash-out fluid in PTC patients.